FORMATION OF FINANCIAL RESOURCES OF ENTERPRISES IN CONDITIONS OF FINANCIAL INSTABILITY - Dmytrovska , V.S. (The actual problems of regional economy development, 2017)
The success of entrepreneurial activity depends on the state of the financial resources of the entity and the choice of the strategy of financial resources forming. In the article the specification of socio-economic nature of the financial resources of enterprises is analyzed and proved , their classification under the relevant characteristics and peculiarities of the financial resources formation of businesses in a rapidly changing economy in the context of sustainable economic state development are given.